Kembar Buncing Under the Awig-Awig of Bali: Kembar Buncing di Kolong Awig-Awig Bali - Wijaya, Guntur Sekti; Islahuddin, Islahuddin (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to explore the relationship between the socio-cultural structure of Balinese customary law and the form of resistance expressed by the main character in the short story Kembar Buncing by Wayan Sunarta. The main issue examined is how cultural values embedded in awig-awig (customary regulations) create social and psychological conflict for the protagonist and how he responds to these cultural pressures through acts of resistance. The short story explicitly represents the reality of a traditional Balinese village society that adheres strongly to myth-based customs, particularly regarding the birth of boy-girl twins (kembar buncing) which is deemed a disgrace when it occurs in families of lower social strata. This condition reflects social inequality within a hierarchical and discriminatory customary structure. This research employs an anthropological literary approach viewing literature as both a reflection and a product of culture as well as a medium for negotiating social values. The theoretical framework positions literature as a representational space of culture and ideology. The study uses a qualitative descriptive method, with close textual analysis focused on narrative elements, conflict, and character dialogue. The hypothesis of this research is that literature serves as a medium of critique against unjust social systems. The character Darsa emerges as a symbol of resistance against outdated customary values that are no longer relevant to contemporary society. The short story portrays the tension between traditional beliefs and modern awareness and reinforcing literature's role as a critical space for challenging cultural hegemony.